2002
DOI: 10.1097/00007890-200201270-00007
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Human-to-Pig Cellular Response by Alteration of Porcine MHC With Human Hla Dpw0401 Exogenes1

Abstract: Our preliminary data demonstrated the possibility that the human HLA DPw0401 phenotype can be transferred onto porcine cells through the generation of HLA transgenic pigs and make the PBMCs of humans more tolerant to porcine cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In summary, as antibody‐ and complement‐driven immune barriers to xenotransplantation are better controlled, approaches to accomplish durable tolerance through T‐cell modulation will become important to safe clinical application. In addition to promising donor cellular and genetic modifications [32,33], CD4 and various costimulation pathways represent logical targets to influence T‐cell responses favorably to achieve this goal. Finally, regulation of other innate immune pathways, such as complement [34], coagulation [31,35], NK cells [36], macrophages [37], and molecular pattern receptors, may prove useful or even necessary to control non‐classical T‐cell activation mechanisms in response to xenoantigens.…”
Section: Invited Commentarymentioning
confidence: 99%
“…In summary, as antibody‐ and complement‐driven immune barriers to xenotransplantation are better controlled, approaches to accomplish durable tolerance through T‐cell modulation will become important to safe clinical application. In addition to promising donor cellular and genetic modifications [32,33], CD4 and various costimulation pathways represent logical targets to influence T‐cell responses favorably to achieve this goal. Finally, regulation of other innate immune pathways, such as complement [34], coagulation [31,35], NK cells [36], macrophages [37], and molecular pattern receptors, may prove useful or even necessary to control non‐classical T‐cell activation mechanisms in response to xenoantigens.…”
Section: Invited Commentarymentioning
confidence: 99%
“…Several years ago, we have successfully generated transgenic pigs for human decay‐accelerating factor (hDAF) and human leukocyte antigen, HLA‐DP and ‐DQ, and confirmed the expression of these transgenes in the pig lines by PCR, RT‐PCR and immuno‐histochemical staining [7–10]. Recently, our group further demonstrated that the human HLA‐DP phenotype could be transferred to pig cells in vitro, and hence the human‐to‐pig cellular response could be reduced [11].…”
Section: Introductionmentioning
confidence: 98%